2016
DOI: 10.17161/bi.v11i1.5053
|View full text |Cite
|
Sign up to set email alerts
|

Completeness of Digital Accessible Knowledge of Plants of Benin and Priorities for Future Inventory and Data Discovery

Abstract: Discovery of and access to primary biodiversity data are critical components in informed decision-making regarding sustainable use of biological resources and conservation of biodiversity. Primary biodiversity data are increasingly available from Benin, but information about completeness of this information across the country is still lacking for most groups. This study analyzed the Digital Accessible Knowledge regarding the plants of Benin to identify gaps in both geographic and environmental dimensions. Many… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 27 publications
4
4
0
Order By: Relevance
“…Our results also showed that protected areas also affect data completeness and that protected areas are less well-inventoried at coarser resolution than at ner resolution (≤ 2500 Km²). Our results are in conformity with those of Ganglo and Kakpo (2016) who found out that plant data completeness in Benin was more effective in protected areas with smaller surfaces.…”
Section: 4-impact Of Accessibility and Protected Areas On Data Comple...supporting
confidence: 93%
See 3 more Smart Citations
“…Our results also showed that protected areas also affect data completeness and that protected areas are less well-inventoried at coarser resolution than at ner resolution (≤ 2500 Km²). Our results are in conformity with those of Ganglo and Kakpo (2016) who found out that plant data completeness in Benin was more effective in protected areas with smaller surfaces.…”
Section: 4-impact Of Accessibility and Protected Areas On Data Comple...supporting
confidence: 93%
“…Our results are supported by those of Ballesteros-Mejia et al (2013) who reported positive effects of tra c access, road density, and tourism on inventory completeness of tropical insects of Sub-Saharan Africa. Our results are also supported by a previous study of Ganglo and Kakpo (2016) on plant data completeness in Benin where they found out that data completeness was positively impacted by the density of roads and waterways. Our results are also in line with those of Kadmon et al (2004) and Souza-Baena et al (2013), in their respective studies on plant species data of Israel and plant data completeness of Brazil where they respectively found out that road bias affected the distribution of data.…”
Section: 4-impact Of Accessibility and Protected Areas On Data Comple...supporting
confidence: 90%
See 2 more Smart Citations
“…In line with the present work, data completeness analyses were diversely achieved at national and regional scales across Africa. In Benin, data completeness analysis was achieved on the DAK of the plants to guide future inventory and data discovery efforts in the country (Ganglo and Kakpo, 2016). From the results obtained, many spatial and environmental gaps exist in the completeness of the data, particularly in the northernmost departments of the country.…”
mentioning
confidence: 99%